Analisis Risiko Proyek Konstruksi Studi Kasus Bendungan Way Sekampung Paket 2 Dengan Metode Failure Mode and Effect Analysis dan Domino - Aftortu, Muhammad Rizqika; Kustiani, Ika; Siregar, Amril Ma'ruf (Universitas Lampung, 2018)
The Way Sekampung Dam construction project is one of the major projects in the province of Lampung. There are several risk involved in the construction of the project. According to Project Management Body of Knowledge (PMBOK), the risks contain in a project can be controlled through risk management. The purpose of this research is to identify and analyze the highest risks in the Way Sekampung Dam package 2 construction project. The data was gathered through a questionnaire that was developed based on previous similar studies. The respondents was recruited based on a purposive sampling method. Based on Failure Mode and Effect Analysis (FMEA) method, it can be concluded three highest occupational risk, namely concrete work in diversion building, tunnel excavation and dewatering work. Subsequently, a fishbone analysis was carried out to determine the basic risk factors. After that a Domino method was utilized to find out the response and efforts to handle those risk.